The Humanistic Value of Ki Hadjar Dewantara's Education in Fine Arts Learning at SMP Taman Dewasa Jetis – Yogyakarta - Mukaddam, Sarah Sabrina; Triyanto, Triyanto; Ibnan Syarif, Muhammad (Catharsis, 2020)
Ki Hadjar Dewantara is a nationalist figure who express his thoughts in education field. Many of his thoughts reflect the existence of a humanist perspective that assume humans as important subjects. This study aims to analyze the humanistic values found in the art of learning at SMP Taman Adults Jetis, Yogyakarta. This study uses qualitative methods with data collection techniques including observation, interviews, documentation, and questionnaires. The data analysis uses data reduction procedures, data presentation, and drawing conclusions (verification). The validity of the data used was a triangulation technique which included triangulation of sources and techniques. The results showed that there were humanistic values in the art of learning which included the following values: (1) solidarity; (2) tolerance; (3) freedom; (4) respect and love, and (5) justice and equality. Based on the results of the research, the researcher can provide suggestions as a material for consideration, so that SMP Taman Dewasa Jetis continued to improve discipline in implementing Ki Hadjar Dewantara's thought-based education, improve work skills for art teachers and students as well as develop teaching materials, methods, and media used.